Determining the taxonomic and functional profile of marine bacterial copper systems involved in marine early copper surface colonization - Gautam, Pratima; Molina, Vanessa; First, Matthew; Erill, Ivan; Cusick, Kathleen D. (Frontiers in Marine Science, 2025)
Copper-based antimicrobial paints are frequently used to inhibit the biofouling of marine vessels. However, some bacterial species can overcome this copper challenge and colonize the surfaces. The early adherent bacterial population of marine vessels plays an important role because of its ability to produce extracellular polymeric substances (EPSs), forming a thin layer of organic matter that traps nutrients from the water and protects other colonizers by blocking the toxic antifouling (AF) coatings. It is of interest to study the factors that drive the initial colonization of copper surfaces. We used a metagenomic sequencing approach to analyze the microbial diversity and potential functional abilities of early biofilm communities on copper surfaces and discovered enriched copper-specific functional traits in early colonizers compared to the bacterial community of the surrounding seawater. The functional analysis of early biofilm colonizers on copper surfaces in marine coastal environments provides insights into molecular mechanisms that support biofilm formation on copper surfaces. The taxa associated with copper resistance traits were found to dominate initial microbial communities on copper surfaces, allowing these organisms to survive on copper surfaces despite copper toxicity. Our analysis reveals the dominance of the genera Allomuricauda and Ruegeria, carrying several copper resistance genes, as the early colonizers of copper surfaces.